Determination of Total Flavonoid Content and Antioxidant Activity Test of Kelakai Stem and Leaf Extract (Stenochlaena palustris (Burm. F) Bedd) - Adi Prayitno; Muthmainah; Helmi Susanti Simamora (Future Science, 2024)
Kelakai plants belong to the Polypodiaceae family and originate from Central Kalimantan. The increasing prevalence of diseases related to oxidative stress has led people to consume natural antioxidants derived from plants. Kelakai plants exhibit antioxidants, anti-inflammatory, and anti-hyperlipidemia activities. Based on these factors, researchers aim to examine the total flavonoid content and determine the antioxidant activity of ethanol extract from the stems and leaves of the kelakai plant (Stenochlaena palustris (Burm. F) Bedd). It is hoped that this study can be an important part of exploring antioxidant compounds obtained from natural materials around us. This study aims to determine the total flavonoid content and understand the antioxidant activity of ethanol extract of Kelakai stems and leaves (Stenochlaena palustris (Burm. F) Bedd). The total flavonoid content was tested using the UV-Vis spectrophotometer method with quercetin standard and expressed in ppm. Meanwhile, the antioxidant activity was determined using the DPPH method, with results expressed in Inhibition Concentration 50% (IC50). The results of the total flavonoid content of ethanol extract were 76.727±0.497 ppm, and the antioxidant activity of ethanol extract of kelakai stems and leaves (Stenochlaena palustris (Burm. F) Bedd) had an IC50 value of 78.787±0.103 ppm, indicating strong intensity and potential